Marketing Strategy of Honey in Sarining Trigona Pertiwi Beekeeper Bongkasa Pertiwi Village - I Gusti Ayu Widari; Aditya Krisnawan Gusti Ngurah (SEAS (Sustainable Environment Agricultural Science), 2022)
Honey bees are one of the potential forest resources to be developed and cultivated. Marketing is an important part of business development. The purpose of this study is to identify of factors that affect honey business cultivation and to obtain the strategy for business development of the business Trigonola Laevicep honey in Sarining Trigona Pertiwi. The method used in this research is the descriptive method using questionnaire, observation, interview, and documentation. The data found were analyzed using descriptive analysis and continued with SWOT analysis. The research found that the main factors contribute for business are as follows; assistance from universities and related institutions, mentoring/training, increasing consumer demand for kele-kele honey, regulations or rules and trends, development of promotional media through social media, the existence of online marketing, the climate and environment supporting the development of honeybee, the availability of natural bee food source plants, and the affordable selling price of kele-kele honey. Several strategies that can be carried out in business development including: Human resources who are highly committed to the development of the kele-kele honey bee cultivation business, assistance from universities and related institutions, kele-kele honey products developed to make derivative products so that consumers can choose more varied products, marketing is done through social media so that the product is more widely known not only in the Bongkasa Pertiwi area, increasing the availability of plants as natural bee food sources, preventing pests and diseases, and the packaging made according to quality standards to ensure the safety of the products.